Pengaruh Pergantian Auditor, Reputasi Kap, dan Komite Audit Terhadap Audit Delay - Riska Damayanti; Kwinlores Sinambela (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the effect of Auditor Change, Public Accounting Firm Reputation, and Audit Committee on Audit Delay. The independent variables in this study are Auditor Change, measured by a dummy variable, Auditor Firm Reputation, measured by a dummy variable, and Audit Committee, measured by the number of Audit Committee members within a company. The dependent variable in this study is audit delay, measured by a dummy variable. This is a quantitative study using secondary data. The population in this study were manufacturing companies in the machinery industry listed on the Indonesia Stock Exchange (IDX) in 2019-2023. Purposive sampling was used, resulting in a sample of 31 companies. The analysis technique used Logistic Regression Analysis. This study employed descriptive statistical data analysis. The results of this study indicate that Auditor Change has no effect on Audit Delay, Public Accounting Firm Reputation does, and Audit Committee has no significant effect on Audit Delay.